Harnessing bacterial strain from rhizosphere to develop indigenous PGPR consortium for enhancing lobia (Vigna unguiculata) production. Issue 3 (March 2023) - Verma, Jay Prakash; Jaiswal, Durgesh Kumar; Gaurav, Anand Kumar; Mukherjee, Arpan; Krishna, Ram; Prudêncio de Araujo Pereira, Arthur
Abstract: The rhizosphere microbes play a key role in plant nutrition and health. However, the interaction of beneficial microbes and Vigna unguiculata (lobia) production remains poorly understood. Thus, we aimed to isolate and characterize the soil microbes from the rhizosphere and develop novel microbial consortia for enhancing lobia production. Fifty bacterial strains were isolated from the rhizosphere soil samples of lobia. Finally, five effective strains (e.g., Pseudomonas sp. IESDJP-V1 and Pseudomonas sp. IESDJP-V2, Serratia marcescens IESDJP-V3, Bacillus cereus IESDJP-V4, Ochrobactrum sp. IESDJP-V5) were identified and molecularly characterized by 16 S rDNA gene amplification. All selected strains showed positive plant growth promoting (PGP) properties in broth culture. Based on morphological, biochemical, and plant growth promoting activities, five effective isolated strains and two collected strains ( Azospirillum brasilense MTCC-4037 and Paenibacillus polymyxa BHUPSB17) were selected. The pot trials were conducted with seed inoculations of lobia (Vigna unguiculata) var. Kashi Kanchan with thirty treatments and three replications. The treatment combination T3 ( Pseudomonas sp. IESDJP-V2), T14 ( Pseudomonas sp. IESDJP-V2 +  A. brasilense ), T26 ( Pseudomonas sp. IESDJP-V1+ B. cereus IESDJP-V4 +  P. polymyxa ) and T27 (IESDJP-V1+ IESDJP-V5+ A. brasilense ) were recorded for enhancing plant growth attributes, yield, nutritional content like protein, total sugar, flavonoid and soil properties as compared to control and others. The effective treatments T3 ( Pseudomonas sp.), T14 ( Pseudomonas sp. IESDJP-V2 +  A. brasilense ), T26 ( Pseudomonas sp. IESDJP-V1+ B. cereus IESDJP-V4 +  P. polymyxa ) and T27 (IESDJP-V1+ IESDJP-V5+ A. brasilense ) recorded as potential PGPR consortium for lobia production. The treatment of single ( Pseudomonas sp.), duel (IESDJP-V2 +  A. brasilense ) and triple combination (IESDJP-V1+ IESDJP-V4 +  P. polymyxa ) and (IESDJP-V1+ IESDJP-V5+ A. brasilense ) can be further used for developing effective indigenous consortium for lobia production under sustainable farming practices. These PGPR bio-inoculant will be cost-effective, environment-friendly and socially acceptable.